Accountability and Transparency in the Management of Village Funds in Sukajaya Village, Kedurang Ilir District, South Bengkulu Regency: Akuntabilitas dan Transparansi Pengelolaan Dana Desa di Desa Sukajaya, Kecamatan Kedurang Ilir, Kabupaten Bengkulu Selatan - Bakirman, Bakirman; Purnawan, Heru; Mulyadi, Mulyadi (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to identify and evaluate the level of accountability and transparency in the management of village funds in Sukajaya Village, Kedurang Ilir Subdistrict, South Bengkulu Regency. The goal is to enhance the effectiveness and integrity of the village fund management and to provide recommendations for improvements to the relevant parties and the village community. This research employs a qualitative descriptive method to investigate accountability and transparency in the management of village funds in Sukajaya Village, Kedurang Ilir Subdistrict, South Bengkulu Regency. Data collection techniques include documentation and in-depth interviews with various informants such as the Village Head, village apparatus, members of the Village Consultative Body (BPD), community leaders, and other villagers. It also utilizes descriptive analysis to systematically organize and interpret the data. The conclusion of this study indicates that although the accountability and transparency of the Village Fund management in Sukajaya Village are quite good, there are several areas that need improvement. These include planning, implementation and supervision, accountability, accessibility of information to the community, community participation in decision-making, as well as reporting and complaints related to the use of the Village Fund.